SCROLLING OR STUDYING? HOW SOCIAL MEDIA AFFECTS THE ACADEMIC PERFORMANCE OF 11–12-YEAR-OLD LEARNERS - qizi, Maxmudova Mashxuraxon Muhammadzokir; qizi, Scientific adviser: Abdusattorova Maxarram Sharifjon (Research Focus International Scientific Journal, 2026)
This study explores how social media affects the academic behavior of 11–12- year-old students. The findings show that students use their phones in a mostly balanced way for communication, entertainment, and sometimes learning. However, using phones during homework can reduce concentration, even if students do not always notice it. Overall, social media is neither fully harmful nor fully beneficial; its impact depends on how consciously students use it.